How young people talk about their variations in sex characteristics: making the topic of intersex talkable via sex education. Issue 5 (3rd September 2021) - Lundberg, Tove; Roen, Katrina; Kraft, Carina; Hegarty, Peter
ABSTRACT: Classrooms are important spaces for young people with variations in sex characteristics and their classmates. Sex education can promote agency and well-being by helping young people make sense of their embodiment and form rewarding social relationships and by changing societal understandings about variations in sex characteristics. Realising this potential however may hinge on how sex education makes intersex (un)talkable. We draw on interviews with 22 young people on how and why they try to make their variation in sex characteristics talkable with others. By focusing on how they talk to others and why they do not talk to others, this research highlights how participants 'fear rejection' but need to talk to others about their variation in the process of 'dealing with it'. Participants also struggle with 'secrecy versus privacy' and how to 'communicate strategically.' Findings acknowledge the emotional work required of people with variations in sex characteristics when making intersex talkable. The analysis points to the role of both talking and silence. We conclude by envisaging a norm-critical sex education that engages with the responsibilities of both talking and listening, shifting the burden away from individual young people with variations in sex characteristics and working towards more mutual social relationships.